Sensory motor mechanisms unify psychology: the embodiment of culture - Soliman, Tamer; Gibson, Alison; Glenberg, Arthur M. (Frontiers in Psychology, 2013)
Sensorimotor mechanisms can unify explanations at cognitive, social, and cultural levels. As an example, we review how anticipated motor effort is used by individuals and groups to judge distance: the greater the anticipated effort the greater the perceived distance. Anticipated motor effort can also be used to understand cultural differences. People with interdependent self-construals interact almost exclusively with in-group members, and hence there is little opportunity to tune their sensorimotor systems for interaction with out-group members. The result is that interactions with out-group members are expected to be difficult and out-group members are perceived as literally more distant. In two experiments we show a) interdependent Americans, compared to independent Americans, see American confederates (in-group) as closer; b) interdependent Arabs, compared to independent Arabs, perceive Arab confederates (in-group) as closer, whereas interdependent Americans perceive Arab confederates (out-group) as farther. These results demonstrate how the same embodied mechanism can seamlessly contribute to explanations at the cognitive, social, and cultural levels.